Contralateral Progression after Unilateral Surgery for Bilateral Chronic Subdural Hematoma: A Prospective Observational Study - Kenji YAGI; Yasukazu HIJIKATA; Yoshifumi TAO; Yoshihiro SUNADA; Ryunosuke HARUTA; Masato MARUNO; Yukari MINAMI; Hisanori EDAKI; Satoshi HIRAI; Satoshi INOUE; Tomohito HISHIKAWA; Masaaki UNO (Neurologia Medico-Chirurgica)
Bilateral chronic subdural hematoma is treated by burr-hole surgery. Patients may undergo simultaneous bilateral surgery, or unilateral surgery which occasionally necessitates subsequent contralateral surgery due to the contralateral chronic subdural hematoma progression. Contralateral chronic subdural hematoma progression is not well understood, and an optimal surgical strategy for bilateral chronic subdural hematoma remains undefined. This study aimed to identify predictors for contralateral chronic subdural hematoma progression following unilateral surgery in patients with bilateral chronic subdural hematoma, specifically examining contralateral chronic subdural hematoma presented as membranous (indicating an older hematoma) and the contralateral hematoma volume. In this prospective observational study, 39 patients with bilateral chronic subdural hematoma requiring surgery were included between February 2020 and July 2024. All patients initially underwent unilateral burr-hole surgery. Additional surgery was performed if contralateral chronic subdural hematoma progression occurred. The preoperative predictors of contralateral chronic subdural hematoma progression were investigated. Among the 39 patients, 16 (41%) experienced contralateral chronic subdural hematoma progression, necessitating contralateral surgery. Of the 12 patients with membranous-type chronic subdural hematoma on the contralateral side, contralateral chronic subdural hematoma progression developed in one patient (8%), whereas 15 (56%) of the 27 patients with non-membranous type had contralateral chronic subdural hematoma progression. Logistic regression analyses revealed that membranous-type hematoma was negatively associated with the risk of contralateral chronic subdural hematoma progression, with an odds ratio of 0.07 (95% confidence interval: 0.01-0.65). Additionally, preoperative hematoma volume on the contralateral side was identified as a risk factor for contralateral chronic subdural hematoma progression, with an odds ratio of 1.58 (95% confidence interval: 1.04-2.40) per 10 mL increase. The membranous type and small volume of contralateral chronic subdural hematoma were associated with a lower risk of contralateral chronic subdural hematoma progression after unilateral surgery in bilateral chronic subdural hematoma. We suggest applying unilateral surgery selectively to bilateral chronic subdural hematoma with these characteristics.